PEAR1 is not a major susceptibility gene for cardiovascular disease in a Flemish population - Wen-Yi Yang; Thibault Petit; Nicholas Cauwenberghs; Zhen-Yu Zhang; Chang-Sheng Sheng; Lutgarde Thijs; Erika Salvi; Benedetta Izzi; Christophe Vandenbriele; Fang-Fei Wei; Yu-Mei Gu; Lotte Jacobs; et al. (BMC, 2017)
Abstract Background Platelet Endothelial Aggregation Receptor 1 (PEAR1), a membrane protein highly expressed in platelets and endothelial cells, plays a role in platelet contact-induced activation, sustained platelet aggregation and endothelial function. Previous reports implicate PEAR1 rs12041331 as a variant influencing risk in patients with coronary heart disease. We investigated whether genetic variation in PEAR1 predicts cardiovascular outcome in a white population. Methods In 1938 participants enrolled in the Flemish Study on Environment, Genes and Health Outcomes (51.3% women; mean age 43.6 years), we genotyped 9 tagging SNPs in PEAR1, measured baseline cardiovascular risk factors, and recorded Cardiovascular disease incidence. For SNPs, we contrasted cardiovascular disease incidence of minor-allele heterozygotes and homozygotes (variant) vs. major-allele homozygotes (reference) and for haplotypes carriers vs. non-carriers. In adjusted analyses, we accounted for family clusters and baseline covariables, including sex, age, body mass index, mean arterial pressure, the total-to-HDL cholesterol ratio, smoking and drinking, antihypertensive drug treatment, and history of cardiovascular disease and diabetes mellitus. Results Over a median follow-up of 15.3 years, 238 died and 181 experienced a major cardiovascular endpoint. The multivariable-adjusted hazard ratios of eight PEAR1 SNPs, including rs12566888, ranged from 0.87 to 1.07 (P ≥0.35) and from 0.78 to 1.30 (P ≥0.15), respectively. The hazard ratios of three haplotypes with frequency ≥10% ranged from 0.93 to 1.11 (P ≥0.49) for mortality and from 0.84 to 1.03 (P ≥0.29) for a cardiovascular complications. These results were not influenced by intake of antiplatelet drugs, nonsteroidal anti-inflammatory drugs, or both (P-values for interaction ≥ 0.056). Conclusions In a White population, we could not replicate previous reports from experimental studies or obtained in patients suggesting that PEAR1 might be a susceptibility gene for cardiovascular complications.